2013
DOI: 10.1242/jeb.073825
|View full text |Cite
|
Sign up to set email alerts
|

Host–parasite molecular cross-talk during the manipulative process of a host by its parasite

Abstract: SummaryMany parasite taxa are able to alter a wide range of phenotypic traits of their hosts in ways that seem to improve the parasiteʼs chance of completing its life cycle. Host behavioural alterations are classically seen as compelling illustrations of the ʻextended phenotypeʼ concept, which suggests that parasite genes have phenotype effects on the host. The molecular mechanisms and the host-parasite cross-talk involved during the manipulative process of a host by its parasite are still poorly understood. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 95 publications
0
56
0
Order By: Relevance
“…Investigation of the mechanisms underlying parasitic manipulation suggests that alteration of the host's neuromodulatory system is a common feature of manipulated hosts (Thompson and Kavaliers, 1994;Adamo, 2002;Adamo, 2013;Helluy, 2013;Lafferty and Shaw, 2013). Indeed, several studies involving both vertebrate and invertebrate hosts have reported altered levels of neuromodulators or neuropeptides concomitant with a parasite-induced change in behaviour (see references in Table1), or changes in expression of genes or proteins linked to biogenic amine metabolism in the brain (Hoek et al, 1997;Biron et al, 2005;Ponton et al, 2006;Prandovszky et al, 2011;Biron, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the mechanisms underlying parasitic manipulation suggests that alteration of the host's neuromodulatory system is a common feature of manipulated hosts (Thompson and Kavaliers, 1994;Adamo, 2002;Adamo, 2013;Helluy, 2013;Lafferty and Shaw, 2013). Indeed, several studies involving both vertebrate and invertebrate hosts have reported altered levels of neuromodulators or neuropeptides concomitant with a parasite-induced change in behaviour (see references in Table1), or changes in expression of genes or proteins linked to biogenic amine metabolism in the brain (Hoek et al, 1997;Biron et al, 2005;Ponton et al, 2006;Prandovszky et al, 2011;Biron, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Their expected complexity also challenges the quest for the proximate mechanisms mediating host behavioural change (Poulin, 1995;Lefèvre et al, 2009;Lafferty and Shaw, 2013). Apart from proteomic studies (Biron, 2013), the study of proximate mechanisms underlying parasitic manipulation has focused on neuromodulatory systems (see Table1). We critically review here the concepts, limitations and prospects in investigating particular neuromodulatory systems to elucidate the mechanisms underlying host manipulation by parasites.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the hostparasite relationship of a host with long life span and a parasite with long infective periods is supposed to create diversity among both hosts and parasites (Best et al, 2010), which could thus re-balance relationship of A. astaci and, at least, its North American hosts in Europe. Environmental conditions could, in their part, also be a driving force of the host-parasite coevolution (Wolinska and King, 2009;Biron and Loxdale, 2013) and thus might also be affecting the aforementioned balance. The indications of a shifted balance between signal crayfish (Pacifastacus leniusculus) and A. astaci in Nordic countries seen as signal crayfish population collapses and severe symptoms of individual crayfish infected with A. astaci (Jussila et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…The indications of a shifted balance between signal crayfish (Pacifastacus leniusculus) and A. astaci in Nordic countries seen as signal crayfish population collapses and severe symptoms of individual crayfish infected with A. astaci (Jussila et al, 2013a). The parasites could also manipulate their host's behavior or physiological processes to ensure that they could compelete their life cycle (Biron and Loxdale, 2013). The PsI-genotype, which is one of the two known genotypes currently causing crayfish plague epidemics in Finland and other Nordic countries, has its original North American host species, the signal crayfish (P. leniusculus), present in Europe (Souty-Grosset et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanistic approach has already been successful and demonstrated neurological and hormonal changes in infected hosts (Lefèvre et al, 2009;Adamo, 2012). One of the most promising approaches has been an inference of the genetic basis of parasite control via proteomics (Biron et al, 2005a;Biron et al, 2005b;Biron and Loxdale, 2013). Here, proteome profiles of hairworms (Nematomorpha, also called Gordian worms) causing crickets to jump into water (so that the worms can exit for mating) revealed a molecular cross-talk between the parasite inside the cricket's abdomen and the brain of the cricket.…”
Section: Introductionmentioning
confidence: 99%